HPLC and GC–MS Analysis of Tunisian Peganum harmala Seeds Oil and Evaluation of Some Biological Activities. (November 2017) - Khadhr, Maroua; Bousta, Dalila; Hanane, El Hajaji; El Mansouri, Latifa; Boukhira, Smahane; Lachkar, Mohammed; Jamoussi, Bassem; Boukhchina, Sadok
Abstract : In this work, we characterized by high-performance liquid chromatography, the γ-tocopherol (573.66 μg/g), and by gas chromatography–mass spectrometry, the linoleic acid (62.05%) as major components from Peganum harmala L. seeds oil and evaluated their potential in vivo acute antiinflammatory, analgesic activities, and in vitro antioxidative capacity. The 2, 2-Diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay showed an important antioxidant activity (62.50% with an IC50 of 4.8 mg/mL). In addition, the antiinflammatory effect of the formulation cream at 20% caused a reduction in inflammation at 5 hours after carrageenan application compared with diclofenac at 1% (60.4%; 45.65%; respectively). A slight potential peripheral analgesia was noted in plantar test in treated rats with cream (20 s). Therefore, our findings demonstrate that formulation cream of P. harmala seeds oil has an interesting antiinflammatory activity with a slight peripheral analgesic effect due mainly to its richness on linoleic acid, γ-tocopherol, and polyphenols and to its important antioxidant capacity.